Hubungan Dukungan Keluarga Terhadap Pemenuhan Kebutuhan Spiritual Pasien Stroke - Nurwahyuni, Nurwahyuni; Amir, Yufitriana; Tampubolon , Nurhannifah Rizky (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: Family support in fulfilling spiritual needs plays a crucial role as a coping source for stroke patients in accepting their illness and treatment process. If families neglect this aspect, it can lead to patients feeling lonely, experiencing prolonged stress, feeling worthless, and feeling abandoned in terms of affection. Therefore, the role of the family is very important for patients so that they feel cared for, supported, comfortable, and at peace. This study aims to determine the relationship between family support and the fulfillment of the spiritual needs of stroke patients. Method: This type of research is quantitative with a cross-sectional approach. This research was conducted at RSUD Arifin Achmad. The population consists of the families of stroke patients. The sample consisted of 110 respondents using accidental sampling technique. The measurement tool used is a questionnaire. The analysis used is bivariate analysis using the chi-square test. Results: The majority in the age group ≥ 55 years were 58.2%, and respondents of male gender were 56.4%, respondents with moderate family support were 58.2%, and respondents with good spiritual needs fulfillment were 56.4%. The chi-square test results showed a relationship between family support and the fulfillment of spiritual needs in stroke patients, with a p-value of 0.009 < 0.05. It is hoped that healthcare workers can provide information to respondents and their families by conducting health education and socializing stroke recovery programs.